PECULIARITY OF SUMMER PHYTOPLANKTON SPATIAL DISTRIBUTION IN THE ONEGA BAY OF THE WHITE SEA UNDER THE LOCAL HYDROPHYSICAL CONDITIONS - T. A. Belevich; L. V. Ilyash; A. V. Zimin; M. D. Kravchishina; A. E. Novikhin; E. D. Dobrotina; Т. А. Белевич; Л. В. Ильяш; А. В. Зимин; М. Д. Кравчишина; А. Е. Новихин; Е. Д. Добротина (Lomonosov Moscow State University, School of Biology, 2016)
The species composition and phytoplankton biomass, concentrations of chlorophyll “a” (Chl) and nutrients in the surface water layer, and concurrent hydrophysical conditions were studied in the Onega Bay of the White Sea during June, 2015. The temperature and salinity of surface water layer and the water column stability varied significantly in the bay. The nutrients concentrations exceeded the threshold limiting of phytoplankton development. The phytoplankton abundance was relatively low, mean values were: total phytoplankton biomass — 13,46±9,00 mg C/m3, concentration of chlorophyll “a” — 0,78±0,43 mg/m3, picophytoplankton biomass — 0,18±0,27 mg C/m3. The highest phytoplankton biomass was found near frontal zones. Structural analysis has revealed three phytoplankton communities that significantly have differed in structure. Видовой состав и биомасса фитопланктона, концентрация хлорофилла “a” и биогенных элементов в поверхностном слое, а также сопутствующие гидрофизические условия были исследованы в Онежском заливе Белого моря в июне 2015 г. Температура и соленость поверхностного слоя, степень стратификации водного столба существенно варьировали по акватории залива. Содержание биогенных элементов превышало пороги лимитирования развития фитопланктона, суммарная биомасса фитопланктона составляла 13,46±9,00 мг С/м3, концентрация хлорофилла “a” — 0,78±0,43 мг/м3; биомасса пикофитопланктона — 0,18±0,27 мг С/м3. Наибольшая биомасса отмечена у фронтальных зон. Выявлено три сообщества фитопланктона, достоверно различающихся по структуре.